RESEARCH OF OAK STANDS IN REZEKNE REGION - Šembele, Ina; Matisovs, Ivars (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2019)
Determine the most suitable place for growing oak, in which soil will have better conditions for their growth.